2006
DOI: 10.1093/jn/136.6.1511
|View full text |Cite
|
Sign up to set email alerts
|

The Rate of Intestinal Glucose Absorption Is Correlated with Plasma Glucose-Dependent Insulinotropic Polypeptide Concentrations in Healthy Men

Abstract: Glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP) both play a role in the control of glucose homeostasis, and GIP is implicated in the regulation of energy storage. The capacity of carbohydrates to induce secretion of these incretin hormones could be one of the factors determining the metabolic quality of different types of carbohydrates. We analyzed the correlation between the rate of intestinal absorption of (starch-derived) glucose and plasma concentrations of GLP-1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
71
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 35 publications
9
71
1
Order By: Relevance
“…The positive relation of GLP-1 response to oral glucose appearance (also found by others [23]) is best explained by the fact that the rate of glucose transfer across the intestinal mucosa is a quantitative determinant of the release of gastrointestinal hormones (43). This conclusion is indirectly supported by the observation that dipeptidylpeptidase intravenous inhibitors, which cause modest increments in endogenous GLP-1 levels, have been shown not to alter gastric emptying (44), whereas the use of GLP-1 analogs delays gastric emptying (45).…”
Section: Obesity Glucose Tolerance and Incretin Effectsupporting
confidence: 70%
“…The positive relation of GLP-1 response to oral glucose appearance (also found by others [23]) is best explained by the fact that the rate of glucose transfer across the intestinal mucosa is a quantitative determinant of the release of gastrointestinal hormones (43). This conclusion is indirectly supported by the observation that dipeptidylpeptidase intravenous inhibitors, which cause modest increments in endogenous GLP-1 levels, have been shown not to alter gastric emptying (44), whereas the use of GLP-1 analogs delays gastric emptying (45).…”
Section: Obesity Glucose Tolerance and Incretin Effectsupporting
confidence: 70%
“…[8][9][10] Additionally, the circulating GIP levels were lower in humans that had ingested starch than in those that had ingested glucose. 17) Taking our results and these earlier reports together, the delay in glucose absorption caused by starch being degraded slowly in the lumen should lead to a reduction in GIP gene expression. It is still unknown which signal altered the GIP mRNA levels in the rats fed on the diet with RS.…”
supporting
confidence: 75%
“…In our studies, 13 Cisotopic enrichment is usually determined with GC/C/IRMS, requiring derivatization of plasma samples prior to analysis (21)(22)(23)(24). Since the introduction of the LC interface for IRMS by Krummen et al (25), several studies showed the power and accuracy of this method in many disciplines (26)(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 87%